ChemInform Abstract: Identification of a New Biflavonoid (I) from Selaginella doederleinii Hieron. Issue 8 (25th February 2014) - Han, Ah‐Reum; Lee, Na‐Youn; Nam, Joo‐Won; Wiryawan, Adam; Seo, Eun‐Kyoung
Abstract isolation and structure elucidation